(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The preservation of historical and cultural monuments as a unit of cultural heritage and as an understanding of the corresponding cultural phenomenon is one of the most pressing global problems in the modern world. To obtain accurate scientific data on the scale of historical and cultural monuments, a modern interpretation of this term is required. This article analyzes the genesis of the phenomenon, the etymology of the term “historical monument”, the specifics of the evolutionary process in the framework of historical milestones in the context of museum research, which emphasizes the modern concept. The new formulation of the model of a monument of history and culture, which is one of the popular definitions of the terminology of museum research, requires careful analysis to fully understand the quintessence of this phenomenon. Extensive research in this area confirms that the definition of “monument of history and culture” developed in a special way in the process of evolution. In this regard, the main objectives of the study are the history of the origin of the definition, its etymology, various shades of its meaning and features of the formulation. The main arguments of the modern essence of this phenomenon, according to the authors, begin with a terminological explanation of the word “monument”, which forms the core of this term and is the aim of studying this article. Key words: monument, cultural heritage, cultural value, museology, study of monuments.